The Effect of Humble Leadership on Organizational Citizenship Behavior and Organizational Misbehavior: The Mediating Role of Work Motivation (A Study at Geblek Pari Kulon Progo) - Faris Ahmad Afif; Majang Palupi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study investigates the impact of humble leadership on organizational citizenship behavior (OCB) and organizational misbehavior, with work motivation as a mediating variable. Conducted at the Geblek Pari Group, the research employed a quantitative approach involving 70 employees as participants. Data were collected through questionnaires using a five-point Likert scale and analyzed with SmartPLS. The results reveal that humble leadership has a positive and significant effect on both work motivation and OCB, while exerting a negative and significant effect on organizational misbehavior. Furthermore, work motivation is confirmed to mediate the relationship between humble leadership and the two behavioral outcomes. The findings suggest important managerial implications: organizations should strengthen humble and participatory leadership practices, particularly in acknowledging employees’ small contributions, implement effective work monitoring systems, and foster a culture of voluntary engagement. These strategies are essential for reducing misbehavior and enhancing organizational effectiveness.